2015
DOI: 10.1016/j.ejbt.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of rice bran hydrolysate to ethanol using Zymomonas mobilis biofilm immobilization on DEAE-cellulose

Abstract: Background:The major challenges associated with the fermentation of lignocellulosic hydrolysates are the reduction in the operating cost and minimizing the complexity of the process. Zymomonas mobilis biofilm has been emerged to resolve these complexities. Biofilm has been reported to tolerate to the toxic inhibitors and easily manipulated toward the cell recycle through the cell immobilization. Results: Z. mobilis ZM4 and TISTR 551 were able to develop biofilms on DEAE cellulose under the differences in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Recent studies showed that Z. mobilis biofilm cells exhibited a higher survival rate and metabolic activity than planktonic or free cells, which can also be developed and applied for the production of valuable bioproducts from toxic lignocellulosic hydrolysates (Li et al 2006;Todhanakasem et al 2014Todhanakasem et al , 2015Todhanakasem et al , 2018.…”
Section: Strategies To Enhance Inhibitor Tolerance Of Z Mobilismentioning
confidence: 99%
“…Recent studies showed that Z. mobilis biofilm cells exhibited a higher survival rate and metabolic activity than planktonic or free cells, which can also be developed and applied for the production of valuable bioproducts from toxic lignocellulosic hydrolysates (Li et al 2006;Todhanakasem et al 2014Todhanakasem et al , 2015Todhanakasem et al , 2018.…”
Section: Strategies To Enhance Inhibitor Tolerance Of Z Mobilismentioning
confidence: 99%
“…The mannitol and polysaccharides were generally increased with the increase of RBH dosage. The increasing polysaccharide production in CM was caused by the abundance of sugars in RBH that can be used as carbon sources for fungus (Todhanakasem et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This work also documented increases in the immobilized cell concentrations for Z. mobilis biofilms on delignified corn silk and increased ethanol productivity in fermentations. Many different abiotic substrates have been used as immobilizers for Z. mobilis in the production of bioethanol, including glass beads, anionic exchangers and polypropylene composite agricultural waste (Krug and Daugulis, 1983;Kunduru and Pometto Iii, 1996;Todhanakasem et al, 2015;Weuster-Botz et al, 1993). The present study is unique in that it is the first work to show the biofilm structure and biofilm forming ability of Z. mobilis on agricultural material, as well as illustrating the potential for enhanced ethanol production from lignocellulosic hydrolysate.…”
Section: Figmentioning
confidence: 85%